Family Counseling and Its Role in Addressing the Phenomenon of Divorce: A Descriptive-Analytical Study on a Sample of Clients at Mawaddah Family Development Association in Jeddah (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to identify the prominent causes of divorce from the perspective of social workers and family counselors in Saudi society. It also sought to determine the post-divorce repercussions on the family and examine the role of family counseling in mitigating this phenomenon. The study adopted the social survey method as an appropriate research methodology. A questionnaire was utilized as the primary tool for data collection, administered to a sample of (30) practitioners and specialists in the Kingdom of Saudi Arabia. Data were analyzed using the Statistical Package for the Social Sciences (SPSS).The findings of the study revealed that the most significant cause of divorce lies in separation occurring after a long marriage due to the accumulation of unresolved issues, which ranked first with a mean of (2.91). Furthermore, the most prominent post-divorce effect on the family was the compounded negative impact on children's stability in the event of weak regulatory agreements between parents, with a mean of (2.87). The results also indicated that the role of family counseling emerges as a decisive factor in reducing divorce, led by the importance of having highly qualified family practitioners and counselors, which yielded a high mean of (2.93). Additionally, the findings showed that all items under the dimension of family counseling’s role in mitigating divorce received a general response level of "Agree." Based on these results, the study recommended the necessity of activating joint coordination pathways between judicial authorities and family counseling centers. It also emphasized designing intensive rehabilitation and therapeutic programs that enhance conflict-resolution and dispute-management skills for spouses, addressing a potential lack of family awareness regarding these aspects.
Keywords: Causes of Divorce; Effects of Divorce; Family Counseling; Social Workers